THE PROBLEMS OF IDENTIFICATION OF THE NEO-PLEISTOCENE GLACIAL MEGA-FLOOD DEPOSITS IN THE ALTAI MOUNTAINS REGION - I. D. Zol’nikov; E. V. Deev (Лëд и снег, 2015)
Similarities and differences of glacial megaflood deposits and deposits of other genetic types of Gorny Altai are considered in the paper. Diluvial sedimentary complex includes (from bottom to top): debris flow facies of boulder-pebbles with giant boulders; floodplain facies of parallel laminated sands and gruss, fluvial cross-bedded pebbles facies, suspension facies of sands and silts; mud flow facies, facies secondary-dammed lake is thin parallel-laminated silts and sands. The deposits of different genetic types may appear similar in facies, textural and structural characteristics, but the geological structure and sedimentary facies architecture of the sediment complexes of various origins (the number of co-observed lithotypes and geologic nature of their relationship) have a specific and recognizable.